Hermeneutika Qur'an Ekofeminis: Upaya Mewujudkan Etika Ekologi al-Qur’an Yang Berwawasan Gender - Shinta Nurani (Religia, 2017)
This paper aims to offer ecological feminism as a concept of environmental ethics by mapping the ecology in Qur’anic’s perspective and Muslim ecofeminist and how to apply hermeneutics Muslims ecofeminist in the verses Qur’an of ecology, and how the contribution of this paper can be formulated ecological ethics of the Qur’an sound gender. This study was analyzed using hermeneutic approach of Gadamer called effective history because in understanding the concept of hermeneutics Qur'an ecofeminist there must be a historical event that is different from the Muslim ecofeminist which will not be separated from the circumstances that surrounded him. Hopefully, through the model hermeneutic interpretation of the ecological verses and the views of Muslim ecofeminist can generate strategic actions resolve the ecological crisis through environmental awareness with the feminine character qualities and how should the mutual relationship between man and God (habl ma’a Allah), man with him own (habl ma’a nafsih), man to man (habl ma’a al-nas), and the man with the universe (habl ma'a al-kawn), regardless of gender specific.